Influence of headache frequency on clinical signs and symptoms of TMD in subjects with temple headache and TMD pain - Anderson, Gary C; John, Mike T; Ohrbach, Richard; Nixdorf, Donald R; Schiffman, Eric L; Truelove, Edmond S; List, Thomas (Pain (Amsterdam), 2011)
The relationship of the frequency of temple headache to signs and symptoms of temporomandibular joint (TMJ) disorders (TMD) was investigated in a subset of a larger convenience sample of community TMD cases. The study sample included 86 painful TMD, nonheadache subjects; 309 painful TMD subjects with varied frequency of temple headaches; and 149 subjects without painful TMD or headache for descriptive comparison. Painful TMD included Research Diagnostic Criteria for Temporomandibular Disorders diagnoses of myofascial pain, TMJ arthralgia, and TMJ osteoarthritis. Mild to moderate-intensity temple headaches were classified by frequency using criteria based on the International Classification of Headache Disorder, 2nd edition, classification of tension-type headache. Outcomes included TMD signs and symptoms (pain duration, pain intensity, number of painful masticatory sites on palpation, mandibular range of motion), pressure pain thresholds, and temple headache resulting from masticatory provocation tests. Trend analyses across the painful TMD groups showed a substantial trend for aggravation of all of the TMD signs and symptoms associated with increased frequency of the temple headaches. In addition, increased headache frequency showed significant trends associated with reduced PPTs and reported temple headache with masticatory provocation tests. In conclusion, these findings suggest that these headaches may be TMD related, as well as suggesting a possible role for peripheral and central sensitization in TMD patients.